Tren dalam Kerja Sama Keamanan Energi Rusia-Tiongkok: Perspektif Negara Produsen - Sagena, Uni W.; Pratiwi, Tiara Rizky; Mujiono, Dadang Ilham K. (Universitas Muhammadiyah Yogyakarta, 2019)
This article aims to explain the important situations and significant changes that show several trends which affect Russian energy cooperation with China. It focused on Vladimir Putin's administration when Russia-China energy cooperation reached significant agreement after being stalled and hampered for years. It was only in his period that Russia made a big decision by showing a soft policy towards China's interests. On the other hand, Russia also showed an aggressive and strong motivation to expand gas cooperation with China. Findings of this article about four significant trends on Russian side: trend on energy policy reform, trend on Gazprom`s role, trend of market expansion to China and Asia, and trend of geographic consideration and border issues. This article is based on Russia perspective by using concept of energy security and the theory of foreign policy making. It uses qualitative explanatory research and concludes that the energy trends underlie the consideration of Russia's energy policy choices toward China. The importance of this article is to understand the perspective of energy producer and as scientific insight into issues of global energy security, specifically about cross border gas pipeline between two giant countries in the world, Russia and China.